Artificial Intelligence‐Enabled Short‐Term Ambulatory Monitoring ECG During Sinus Rhythm for Prediction of Hidden Atrial Fibrillation. - Chang, Ting‐Yung; Chen, Song‐Po; Hsieh, Jui‐Hung; Huang, Guan‐Jun; Hung, King‐Chu; Guo, Shu‐Mei; Liu, Chih‐Min; Chang, Shih‐Lin; Lin, Yenn‐Jiang; Lo, Li‐Wei; Hu, Yu‐Feng; Chung, Fa‐Po; et al. (Journal of Cardiovascular Electrophysiology, 2025)
Background: Screening of asymptomatic/occult atrial fibrillation (AF) remains challenging. This study aimed to use a deep learning model to predict hidden AF in patients who showed normal sinus rhythm (SR) during 24‐h Holter monitoring. Methods: This was a retrospective cohort study that enrolled 934 patients receiving 24‐h ambulatory Holter monitoring. Of them, 640 patients (AF group) had the documented paroxysmal AF in the index Holter monitoring. The rest of 294 patients (Control group) did not have medical record of AF and the index Holter exam did not detect AF. A ConvNeXt model (1st stage) and Long Short‐Term Memory (LSTM) (2nd stage) was used to predict the probability of AF. Results: 368,550 eligible SR ECG segments (60 s/segment) were taken into 1st staged classification, and the Area Under Curve (AUC) was 0.7755 with accuracy of 0.7755, sensitivity of 0.9105, and specificity of 0.5718. After 2nd staged classification (10‐min SR ECG recording), the AUC reached 0.874 (accuracy of 0.8213, sensitivity of 0.8339, and specificity of 0.8115). The fact that longer time length examined in the 2nd stage leaded to a dilution of features more related to AF might decrease specificity compared with 1st stage. Subgroup analysis demonstrated that night‐time settings had better performance (AUC: 0.902 in night‐time, 0.8726 in day‐time). Conclusion: We developed an AI‐enabled model with 10 min ECG recording from ambulatory Holter monitoring during SR to predict hidden AF with high accuracy. Subgroup analysis according to the diurnal period, night‐time settings showed more favorable performance compared to day‐time recordings.